Implementation of a dominance protocol for wireless medium access - Pereira, Nuno (2014)
Consider the problem of scheduling sporadic message transmission requests with deadlines. For wired channels, this has been achieved successfully using the CAN bus. For wireless channels, researchers have recently proposed a similar solution; a collision-free medium access control (MAC) protocol that implements static-priority scheduling. Unfortunately no implementation has been reported, yet. We implement and evaluate it to find that the implementation indeed is collision-free and prioritized. This allows us to develop schedulability analysis for the implementation. We measure the response times of messages in our implementation and find that our new response-time analysis indeed offers an upper bound on the response times. This enables a new class of wireless real-time systems with timeliness guarantees for sporadic messages and it opens-up a new research area: schedulability analysis for wireless networks.